Penerapan Model Cooperative Tipe Jigsaw untuk Meningkatkan Hasil Belajar Siswa pada Mata Pelajaran Matematika - Halimah (MADRASCIENCE: Jurnal Pendidikan Islam, Sains, Sosial, dan Budaya, 2022)
The problem faced by the teacher is the low mastery of students on the material. The subjects in this learning improvement were the sixth-grade students of SD Negeri 001 Singkep Barat, totaling 22 students consisting of 11 male students and 11 female students. The objectives of this learning improvement process are: 1) To determine the effect of the jigsaw cooperative method on the learning outcomes of sixth grade students of SD Negeri 001 Singkep Barat; 2) Whether or not there is an interaction between the jigsaw type cooperative method and the students' interests; 3) Improving the ability of teachers in teaching; 4) Creating active and interactive learning. This learning improvement research applies the jigsaw type of cooperative method using quantitative, qualitative and observational techniques. This learning improvement was carried out in 2 cycles. From the results of the improvement in learning in cycle 1 the percentage of completeness was 77.27%, while in cycle 2 it increased to 100%. The data shows an increase in students' understanding and mastery of the material. It can be concluded that learning mathematics using the jigsaw type cooperative method can improve students' learning achievement.